Kedudukan Seni dalam Islam: Telaah Literatur tentang Nilai, Estetika dan Etika Seni Islam - Intan Pratama Mukti; Lisma Mardiyah; Mimah Mahmudah; Muhamad Fadly Al Bahry; Abdul Azis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the role of art in Islam by revisiting various books and references that focus on three main aspects: values, aesthetics, and ethics. In Islamic perspective, art is not merely about expressing beauty, but also serves as a medium to enhance one’s faith and morality, guiding humans to draw closer to Allah SWT. This research employs a qualitative descriptive approach using a literature review method based on relevant scholarly sources and academic documents. The findings indicate that Islamic art is built upon the principles of tawhid (monotheism), morality, and spirituality, which provide a profound meaning to every artistic creation. In terms of aesthetics, Islamic art emphasizes not only physical beauty but also harmony, balance, and the magnificence of Allah’s creation. The ethical aspect functions as a guideline for artists to ensure that their works remain within the boundaries of Islamic law and serve as instruments of da’wah, education, and moral development. Therefore, Islamic art represents the synthesis of beauty, truth, and goodness that guides humanity toward worship and devotion to Allah SWT. This study concludes that Islamic art plays a vital role in strengthening spirituality, character, and the advancement of an Islamic civilization that is cultured, beautiful, and meaningful.